A NOVEL ASSESSOR FORDISTRIBUTION SYSTEMRELIABILITY - ROUINA, A.; ABOUBOU, A.; ABDELAZIZ, A.; ELHABACHI, A. (Courrier du Savoir; Vol. 13 (2012): Courrier du Savoir, 2014)
Reliability is a key aspect of power system design and planning. This research presents a reliability analysis algorithm for radial operated (with respect to substation), reconfigurable, electrical distribution systems. The algorithm takes into account equipment power handling constraints. Linked lists of segments are employed in obtaining the rapid convergence. The study presented here evaluates improvement of reliability for static load models. A new reliability index is proposed. The proposed index makes easier to locate areas where reliability needs to be improved. Reliability indices for load points and the overall system have been developed.